ANALISIS PENGARUH PEMBERIAN SHELTER TERHADAP TINGKAT KEHIDUPAN BENIH IKAN GURAMI (Oshpronemus Gouramy) ANALYSIS OF THE EFFECT OF SHELTER ON THE SURVIVAL RATE OF GOURAMY (Oshpronemus Gouramy) - rahman, Fathor; Sugiono, Sugiono; Ekalaturrahmah, Yenni Arista Cipta (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
Gouramy seeds are very susceptible to changes in water quality and are easily stressed, the solution is to provide shelter as a place for gouramy fish to take shelter. This study aims to determine the effect of providing shelter on the survival rate of gouramy (Oshpronemus gouramy) fry. The method used in this study was an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The treatments were control, the number of shelters 10 units, 20 units and 30 units. The survival rate data were analyzed using a regression test and continued with a correlation test. Based on the results of the study, the treatment with the highest survival rate was 20 units (99,09%), then 30 units (98,63%), 10 units (98,63%) and the lowest survival rate was control (94,44%). The results of the analysis of variance showed that the provision of shelter had a significant effect on the survival rate of gouramy fry (α= 0,05).